Consumer perceptions of safety in hospitals - Smith Brian J; Berry Jesia G; Evans Sue M; Esterman Adrian J (BMC, 2006)
Abstract Background Studies investigating adverse events have traditionally been principally undertaken from a medical perspective. The impact that experience of an adverse event has on consumer confidence in health care is largely unknown. The objectives of the study were to seek public opinion on 1) the rate and severity of adverse events experienced in hospitals; and 2) the perception of safety in hospitals, so that predictors of lack of safety could be identified. Methods A multistage, clustered survey of persons residing in South Australia (2001), using household interviews (weighted n = 2,884). Results A total of 67% of respondents aged over forty years reported having at least one member of their household hospitalised in the past five years; with the average being two hospital admissions in five years. Respondents stated that 7.0% (95%CI: 6.2% to 7.9%) of those hospital admissions were associated with an adverse event; 59.7% of respondents (95% CI: 51.4% to 67.5%) rated the adverse event as really serious and 48.5% (95% CI: 40.4% to 56.8%) stated prolonged hospitalisation was required as a consequence of the adverse event. Perception of safety in hospitals was largely affected by the experience of an adverse event; really serious events were the most significant predictor of lack of safety in those aged 40 years and over (RR 2.38; p<0.001). Conclusion The experience of adverse events negatively impacted on public confidence in hospitals. The consumer-reported adverse event rate in hospitals (7.0%) is similar to that identified using medical record review. Based on estimates from other studies, self-reported claims of adverse events in hospital by consumers appear credible, and should be considered when developing appropriate treatment regimes.